Design and development of simultaneous EEG-fMRI data acquisition setup to observe brain activity - Ahmad, R.F. (Institute of Electrical and Electronics Engineers Inc., 2014)
EEG and fMRI are non-invasive imaging modalities widely used to understand the brain functions and dysfunction in cognitive neuroscience. EEG provides us the high temporal resolution while functional MRI gives very high spatial resolution and vice versa. To get the better spatiotemporal resolution of human brain neural activities, simultaneous EEG-fMRI data acquisition provides solution to the problem. The development requires MRI compatible EEG equipment which can be successfully integrated and synchronized to make the setup concurrent. In this paper, we discussed some real issues during data acquisition and how to optimize the setup for better SNR. We have developed the simultaneous EEG-fMRI setup at hospital Universiti Sains Malaysia (USM) and also successfully recorded the EEG-fMRI data simultaneously for event related design. Â© 2014 IEEE.